2009
DOI: 10.1002/jbm.b.31368
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic sealant based on gelatin and microbial transglutaminase: An initial in vivo investigation

Abstract: The potential of an in situ gel-forming adhesive was examined as a hemostatic surgical sealant. The gel-forming mechanism for this adhesive mimics the last stages of blood coagulation but uses nonblood proteins. Specifically, gelatin is used as the structural protein and a calcium-independent microbial transglutaminase (mTG) is used as the crosslinking enzyme. In vitro burst pressure tests with porcine skin demonstrate that the gelatin-mTG adhesive forms a gel within 30 min under moist conditions and this gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 106 publications
0
51
0
Order By: Relevance
“…Gelatin sponge is usually produced by chemical crosslinking and subsequent technical processing, including oriented compression, etc. 4,21,22 In the present study, zein, a hydrophobic protein, was co-electrospun with gelatin to obtain hybrid fibrous membranes. The zein skeleton component maintained structural integrity in contact with PBS without crosslinking.…”
Section: Discussionmentioning
confidence: 99%
“…Gelatin sponge is usually produced by chemical crosslinking and subsequent technical processing, including oriented compression, etc. 4,21,22 In the present study, zein, a hydrophobic protein, was co-electrospun with gelatin to obtain hybrid fibrous membranes. The zein skeleton component maintained structural integrity in contact with PBS without crosslinking.…”
Section: Discussionmentioning
confidence: 99%
“…Gelatin gels can adhere to both moist and wet tissues with a comparable or superior adhesive strength to fibrin-based sealants [17][18][19]. Liu et al [64] have found that adhesives produced from mTGasecrosslinked gelatin were able to (i) gel in situ within a relevant timeframe (\5 min), (ii) adhere to tissue in the presence of modest amounts of blood, and (iii) possess appropriate mechanical strength to serve as a hemostatic sealant. According to the same approach, Chen et al [18] examined the potential of the gelatin-mTGase adhesive for ophthalmic applications and especially for vitrectomy procedures for retinal reattachment.…”
Section: Transglutaminase In Biomedical Applicationsmentioning
confidence: 98%
“…Gelatin-based sealants have been created using different crosslinking agents, such as genipin [18], water-soluble carbodiimides [18,19], transglutaminase [20,21], biopolymers [22][23][24] and glutaraldehyde [25]. The use of chemical crosslinking agents has a risk of cytotoxicity caused by the unreacted compounds and their degradation products.…”
Section: Surgical Hemostatic Agentsmentioning
confidence: 99%